Manufacturing and Biological Potential of Saliva‐Loaded Core‐Sheath Pressure‐Spun Polymeric Fibers - Vansh Thukral; Nanang Qosim; Andre Kurniawan; Merve Gültekinoğlu; H.M. Thushari U. Herath; Gareth R. Williams; Mohan Edirisinghe (Macromolecular Materials and Engineering)
Abstract The rich array of antimicrobial components in saliva offers alternative treatments for drug‐resistant bacteria. One therapeutic challenge associated with the effective delivery of salivary components is the quick degradation of salivary proteins outside the oral environment. In this study, polyethylene oxide (sheath) and polycaprolactone (core) based fibers are successfully synthesized using the pressurized gyration technique. Six different pressure‐spun fibers are produced. These fibers are created by varying the quantity of artificial saliva in the sheath layer. This unique and effective methodology of embedding saliva within the sheath of the fiber exhibits enhanced bacterial inhibition against Escherichia coli and Staphylococcus aureus with 80% and 78% inhibition efficiency, respectively. This study showcases a novel technique for promoting wound healing, utilizing core‐sheath fibers, which have tremendous potential because of their superior antimicrobial properties, while also aiding in the process of epithelialization. In vitro, cytotoxicity test results showed that there is no cytotoxic effect on the fibroblast cell line. As a result, it is evaluated that the produced fiber meshes can be ideal wound dressing material, considering their lack of toxic effects and high antibacterial activity levels.